Pengaruh Konseling KB Terhadap Pemilihan Alat Kontrasepsi Pada Ibu Nifas Di BLUD UPT Puskesmas Kaduhejo Tahun 2022: The Effect of Family Planning Counseling on the Selection of Contraceptive Devices for Postpartum Mothers at the UPT Health Center Kaduhejo BLUD in 2022 - Wulan, Ayi Dayu (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: As technology and science development, the world's population also grows seven times. Indonesia is ranked 4th with the largest population in the world. One of the government's efforts to suppress the rate of population growth in Indonesia is the Family Planning Program (KB). The purpose of this study was to determine the effect of counseling on the selection of contraceptives for postpartum mothers at the BLUD UPT Health Center Kaduhejo in 2022. Methods: The current method is a one-group pre-test and post-test design. The population of postpartum mothers in BLUD UPT Health Center Kaduhejo period May-June with a total of 124 people, and with a sample of postpartum mothers in June 55 people. Data were taken using a family planning counseling questionnaire. Data were analyzed by T-Test (paired sample T-test). Results: The results of the study show that counseling is very useful in determining the choice of family planning. This happens because through counseling clients can see the problem more clearly so they can choose their own way out according to the information that has been received, previously. From the results of the study, it can be concluded that there is a difference between the group that was given counseling and the group that was not given counseling with p < 0,05. Discussion: Based on the results of the analysis and conclusions, the authors propose the following suggestions: it is hoped that midwives will improve the quality of the counseling provided so that it affects the stability of acceptors in choosing family planning, it is hoped that this thesis can be used as a reading source or reference to improve the quality of midwifery education, for further researchers, it can be used as a reference. references or readings for further research and can develop this research.